Pengaruh Reward Dan Punishment Terhadap Motivasi Kerja (Studi Kasus Pada Mitra Driver Gojek Kota Malang). - Mochammad Sonif Afiffudin; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to analyze and explain the effect of reward and punishment on work motivation by taking a case study on Gojek Driver Partners in Malang City. The sample collection method in this study was using the Slovin formula and found a sample of 92 respondents. By using multiple linear regression analysis, and the results of the study show that the effect of reward and punishment has a significant effect on work motivation. The method used in data processing uses a quantitative approach with multiple linear regression analysis tools through the SPSS 25 application program. Keywords: Reward, Punishment, and Work Motivation